2010
DOI: 10.1128/jvi.00410-10
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Vaccine-Elicited Nonneutralizing Antienvelope Antibody Activities Contribute to Protective Efficacy by Reducing both Acute and Chronic Viremia following Simian/Human Immunodeficiency Virus SHIV89.6PChallenge in Rhesus Macaques

Abstract: We have shown that following priming with replicating adenovirus type 5 host range mutant (Ad5hr)-human immunodeficiency virus (HIV)/simian immunodeficiency virus (SIV) recombinants, boosting with gp140 envelope protein enhances acute-phase protection against intravenous simian/human immunodeficiency virus (SHIV) 89.6P challenge compared to results with priming and no boosting or boosting with an HIV polypeptide representing the CD4 binding site of gp120. We retrospectively analyzed antibodies in sera and rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
180
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(194 citation statements)
references
References 64 publications
13
180
1
Order By: Relevance
“…23 -27 A recent immunization study in rhesus macaques has demonstrated that HIV-specific Abs could control infection by Ab-dependent cellular cytotoxicity, Ab-dependent cellmediated virus inhibition, and transcytosis-inhibition mechanisms. 74 Indeed, there was a strong correlation between viremic control and inhibition of transcytosis by rectal IgA, whereas the nAb response did not correlate with control of viral load. 74 Furthermore, unlike IgG, high titers of systemic IgA are not as concerning as it is non-inflammatory by nature and does not activate complement by acting through the inhibitory Fc receptor.…”
Section: Articlesmentioning
confidence: 95%
See 1 more Smart Citation
“…23 -27 A recent immunization study in rhesus macaques has demonstrated that HIV-specific Abs could control infection by Ab-dependent cellular cytotoxicity, Ab-dependent cellmediated virus inhibition, and transcytosis-inhibition mechanisms. 74 Indeed, there was a strong correlation between viremic control and inhibition of transcytosis by rectal IgA, whereas the nAb response did not correlate with control of viral load. 74 Furthermore, unlike IgG, high titers of systemic IgA are not as concerning as it is non-inflammatory by nature and does not activate complement by acting through the inhibitory Fc receptor.…”
Section: Articlesmentioning
confidence: 95%
“…74 Indeed, there was a strong correlation between viremic control and inhibition of transcytosis by rectal IgA, whereas the nAb response did not correlate with control of viral load. 74 Furthermore, unlike IgG, high titers of systemic IgA are not as concerning as it is non-inflammatory by nature and does not activate complement by acting through the inhibitory Fc receptor. 75,76 There is ample evidence implicating the importance of " immune quiescence " in maintaining HIV resistance in highly exposed persistently seronegative individuals, 77 -80 and in fact, systemic or mucosal inflammation as a result of immune activation may increase the risk of HIV transmission and pathogenesis.…”
Section: Articlesmentioning
confidence: 95%
“…First, studies in HIV-1-infected people (8)(9)(10)(11)(12)(13)(14) and in macaques infected with simian immunodeficiency virus (15,16) consistently show an inverse correlation between Fc-mediated effector functions, including antibody-dependent cell-mediated cytotoxicity (ADCC) (8,9) or antibody-dependent cell-mediated viral inhibition (ADCVI), and viral loads or decreased disease progression (17). Second, vaccine-elicited protection both in nonhuman primates (18)(19)(20)(21) and in a subset of human subjects in the Vax-004 trial (22) correlates with Fc-mediated effector function often observed in the absence of detectable neutralizing antibodies (18)(19)(20)(21). Similarly, there was an inverse relationship between acquisition of HIV-1 and ADCC in the RV144 trial for a subset of subjects who had low to moderate IgA anti-gp120 titers (23).…”
mentioning
confidence: 99%
“…This interaction induces both degranulation to release perforin/granzymes as well as secretion of antiviral cytokines such as IFN-g and TNF-a. Nonneutralizing Abs have been shown to have an important role in several virus infection models (19)(20)(21)(22).…”
mentioning
confidence: 99%